A world of letters : Yale University Press, 1908-2008 - Basbanes, Nicholas A., 1943- (Yale University Press, 2008)
For Yale University Press, which celebrates its hundredth birthday in 2008, the century has been an eventful one, punctuated with no few surprises. The Press has published more than 8,000 volumes through the years, scores of bestsellers and award-winners among them, and these books have come to fruition through the efforts of a host of colorful authors, editors, directors, board members, and others of intellectual and literary renown. With an ear always cocked for an interesting tale, one of today's best storytellers presents an anecdote-rich chronicle of the Press's first 100 years. Nicholas Basbanes, whom David McCullough has called "the leading authority of books about books," quickly convinces us that the Press's history, while bookish, is also lively and fascinating. Basbanes explores the saga behind the acquisition of Eugene O'Neill's blockbuster play, the all-time Yale bestseller Long Day's Journey into Night; the controversy sparked in 1965 by publication of The Vinland Map; the origins of the groundbreaking Annals of Communism series, initiated in the wake of the Soviet Union's demise; and many more highlights from Press annals. Basbanes looks at the reasons behind the publisher's remarkable financial success, and he completes A World of Letters with a glimpse at the new initiatives that will propel the Press into a second exciting century.